Extract of Rhoeo Discolor Leaf as a Reducing and Stabilizing Agent in the Synthesis of Silver Nanoparticles - Gusrizal, Gusrizal; Sayekti, Endah; Radianti, Sri (Molekul, 2023)
Silver nanoparticles (AgNPs) have been synthesized using Rhoeo discolor leaf extract as a reducing and stabilizing agent. AgNPs were synthesized by adding silver nitrate to the extract of Rhoeo discolor and incubating it in a boiling water bath. The change in color of the mixture from clear to yellow indicated AgNPs formation. The synthesized AgNPs were spherical and showed an absorption peak at around 410-420 nm. The size of particles was distributed from 92 to 485 nm with an average size of 176 nm, and the polydispersity index was 0.185. The stability test showed that synthesized AgNPs were stable for three months of storage at ambient temperature. The extract of Rhoeo discolor were responsible for reducing silver ion and stabilizing the synthesized AgNPs.